Neoadjuvant Pembrolizumab and Chemotherapy in Resectable Esophageal Cancer: An Open-Label, Single-Arm Study (PEN-ICE) - Duan, Hongtao; Shao, Changjian; Pan, Minghong; Liu, Honggang; Dong, Xiaoping; Zhang, Yong; Tong, Liping; Feng, Yingtong; Wang, Yuanyuan; Wang, Lu; Newman, Neil B.; Sarkaria, Inderpal S.; et al. (Frontiers in Immunology, 2022)
Background: In this single-arm study, the efficacy and safety of neoadjuvant pembrolizumab plus chemotherapy were evaluated in patients with resectable esophageal squamous cell carcinoma (ESCC). Methods: This study included patients with ESCC of clinical stage II–IVA who underwent surgery within 4 to 6 weeks after completing treatment with pembrolizumab (200mg) combined with a conventional chemotherapy regimen (3 cycles). The safety and efficacy of this combination treatment were evaluated as primary endpoints of the study. Results: From April 2019 to August 2020, a total of 18 patients (including 14 men) were enrolled, of whom 13 patients progressed to surgery. Postoperative pathology revealed a major pathological response in 9 cases (9/13, 69.2%) and a pathological complete response in 8 cases (6/13, 46.2%). Five patients (5/18, 27.8%) experienced serious treatment-related adverse events of grade 3–4. At the time of data cutoff (Dec 31, 2021), the shortest duration of follow-up was 15.8 months. Programmed death-ligand 1expression in pretreatment specimens was not significantly associated with the percentage of residual viable tumor (RVT) (r=-0.55, p=0.08). Changes in counts of CD68+ macrophage between pre- and post-treatment specimens were weakly correlated with RVT (r=0.71; p=0.07), while a positive correlation was observed between postoperative Foxp3+T cells/CD4+Tcells ratios and RVT (r=0.84, p=0.03). Conclusion: The combination of neoadjuvant immunotherapy and chemotherapy for ESCC is associated with a high pathological response and immunologic effects in the tumor microenvironment. It has acceptable toxicity and great efficacy, suggesting a strong rationale for its further evaluation in randomized clinical trials. KEYWORDS: pembrolizumab; chemotherapy; resectable esophageal cancer; efficacy; safety; pathological complete response (pCR); major pathological response (MPR).